Perubahan Konstitusi dan Reformasi Ketatanegaraan Indonesiaa - Abu Tamrin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2015)
Abstract: Amendment of the Constitution and constitutional reform in Indonesia. The Constitution can be two meanings, namely: a broad sense and narrow sense. Meaning constitution means forming. Constitutional expert in Constitutional Law contains basic law is written. Act of 1945 is a formal document which is the result of political struggle in the past. In the era of the New Order Act of 1945